De houding van jongeren ten aanzien van holebi-rechten : een kwantitatieve en kwalitatieve analyse - Hooghe, Marc; Quintelier, Ellen; Claes, Ellen (Leuven : KU Leuven, 2007)
Fonds Suzan Daniel (FSD)
Nederlands
Monografie